Beliefs and experiences about immunization among refugees resettled in the United States from the Thailand-Myanmar (Burma) border. Issue 4 (4th July 2021) - Truman, Tessa; Higham, Rebecca; Chernenko, Alla; Ahmmad, Zobayer; Pye, Mu; Sin, Kai; Griffiths, Adrienne; Kamimura, Akiko
ABSTRACT: The purpose of this study was to investigate immunization-related experiences among Karen and Karenni refugees from the Thai-Myanmar border currently living in the U.S. Exploration of knowledge, beliefs, and experiences of immunization among Karen and Karenni refugees will help strategize education programs to enhance immunization. Karen and Karenni refugees resettled in the United States from the Thai-Myanmar (Burma) border (n = 120) completed a survey on their perceptions and experiences related to immunizations. Older age was associated with higher levels of perceptions that immunizations were safe and longer-term residence in the U.S. was associated with lower levels of perceptions that immunizations were safe. While long-term side effects of immunizations are not commonly perceived, perceived short-term side effects are prevalent. With improved understanding of demographic factors related to immunization belief and perception, the healthcare system in the United States can strategize culturally fit intervention programs that alleviate potential concerns Karen and Karenni refugees might have regarding vaccination.